Personified Language Style in Poetry Collections and Their Relevance in Indonesian Language Learning in Junior High School - Suryaningsih, Lili; Ariska, Yuyun (Journal of English Language and Education, 2025)
The personified language style is the target in this research, which is to describe how the language style personified by Boy Candra, especially the meaning of the personified language style in the poem by Boy Chandra in the book Ku Ajak Kau Ke Hutan and Tersesat Berdua. The problems answered in this study include avoiding excessive impressions, maintaining balance, difficulty creating personifications between the original and clichés in identifying and classifying personifications consistently, especially the use of ambiguous language. The purpose of describing the language style personified in the poem by Boy Chandra in the books Ku Ajak Kau Ke Hutan and Tersesat Berdua. The approach used, namely a descriptive method, was used to analyze the personified language style in the poem by Boy Chandra in the books Ku Ajak Kau Ke Hutan dan Tersesat Berdua and its relevance in learning Indonesian Language Literature in junior high school. Then it is analyzed using the technique of watching and taking notes, interviews, observations and documentation. Then it is analyzed using data reduction techniques, presentation of conclusive data. This study concluded that several personified language styles were found used by Boy Chandra in the books Ku Ajak Kau Ke Hutan and Tersesat Berdua. Personification is very relevant in poetry learning in junior high school because it helps students understand and understand the meaning of poetry more deeply, develops their creativity in language, and makes poetry feel more alive and interesting. This style of language teaches students to see inanimate objects as if they were alive, which can increase their empathy and imagination, as well as make learning poetry richer and less monotonous.